Annex 1: Research Proposal Evaluation Guideline for Master Students - Editor, The (Himalayan Journal of Sociology and Anthropology, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400;} --> <!--[endif] --> This guideline was presented by Dr. B.K. Parajuli in a workshop organized by the department on May 2006. Faculties of the Sociology/Anthropology, PN Campus, Pokhara have been actively participated, discussed and finalized the guideline during the workshop. The editors of current issue are thankful to Dr. B.K. Parajuli and Mr. Damodar Tripathi for materializing this document. DOI: http://dx.doi.org/10.3126/hjsa.v3i0.1503 Himalayan Journal of Sociology and Anthropology Vol.III, Sept. 2008 p.166-173